Evolution and Implementation of the Delphi Method in Archival Theory and Practice (Atlanti +, 2026)
Purpose: The article examines whether, and in what ways, the Delphi method is methodologically appropriate for addressing contemporary challenges in archival theory and practice, particularly those arising from digital transformation, technological change, and the growing complexity of archival decision making. Method/Approach: The study adopts a qualitative, exploratory research design based on a systematic review and analytical synthesis of methodological and empirical literature. Sources were identified through the Scopus, Emerald Insight, and Springer Nature Link databases and complemented by foundational literature to capture the theoretical origins, development, and variants of the Delphi method. A comparative analysis of major Delphi variants (classical, modified, policy, decision, real-time, argument, and disaggregative) was conducted to assess their methodological characteristics and applicability to specific archival research domains. Results: The analysis demonstrates that the Delphi method is well suited to archival research problems characterized by uncertainty, limited empirical evidence, and normative judgment. Different Delphi variants address distinct research needs: classical and modified Delphi support consensus building, policy, and argument Delphi structure normative and legal debates, while real-time and disaggregative Delphi facilitate rapid iteration and scenario-based analysis. Evidence from published applications confirms the method’s relevance for appraisal, preservation, access, governance, and technology-related archival research. Conclusions findings: The article concludes that the Delphi method constitutes a flexible and robust methodological framework for archival science, offering practical guidance for selecting appropriate Delphi variants in future archival research and interdisciplinary studies.
Keywords: Delphi method; origin and variants of Delphi method; archival science; research methodology; digital archives